2016
DOI: 10.1017/s0954579416001255
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic associations between reading and attention-deficit/hyperactivity disorder dimensions in adolescence

Abstract: Multiple studies have shown that reading abilities and attention-deficit/hyperactivity disorder symptoms, mainly inattention symptoms, are phenotypically and genetically associated during childhood. However, few studies have looked at these associations during adolescence to investigate possible developmental changes. The aim of the study is to examine the genetic and environmental etiology of the associations between inattention and hyperactivity reported by parents, and reading accuracy, reading speed, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Language deficits in early childhood were positively associated with physical aggression in childhood as well as in adolescence [40], whereas hyperactivity was associated with visuospatial organisation deficits [40]. Another study identified that inattention, rather than hyperactivity, was a modestly significant predictor of reading accuracy and speed during adolescence [77]. Family characteristics (e.g., maternal depression symptoms and IQ) have been found to be associated with lower levels of verbal abilities in middle childhood [78].…”
Section: Cognitive Development School Readiness and Educational Achievementmentioning
confidence: 99%
“…Language deficits in early childhood were positively associated with physical aggression in childhood as well as in adolescence [40], whereas hyperactivity was associated with visuospatial organisation deficits [40]. Another study identified that inattention, rather than hyperactivity, was a modestly significant predictor of reading accuracy and speed during adolescence [77]. Family characteristics (e.g., maternal depression symptoms and IQ) have been found to be associated with lower levels of verbal abilities in middle childhood [78].…”
Section: Cognitive Development School Readiness and Educational Achievementmentioning
confidence: 99%
“…Approximately 20–40% of children with the inattentive subtype of ADHD have RD ( 50 , 51 ) and 20–40% of those with RD have ADHD ( 33 ). The relationship between ADHD symptoms and reading is found to be predominantly in the inattentive type ( 30 , 31 ). Neuropsychological profiles of RD and ADHD comorbid groups include deficits in processing speed, verbal working memory, phonological short-term memory, naming speed, and central executive processes ( 32 , 33 ).…”
Section: Comorbid Mental Disordersmentioning
confidence: 99%
“…Sin embargo, los niños DA y DD+DA tuvieron puntuaciones significativamente más altas de errores, pero menos problemas en la fluidez que DD sola. En conclusión, el subtipo inatento de TDAH comparte con la DD las dificultades de lectura, persistentes hasta la adolescencia (Plourde, et al, 2017), pero las dificultades en la lectura concurrentes con DA no siempre están asociadas al déficit en la conciencia fonológica. Borella et al (2011) concluyen que la dificultad en la escritura tampoco es específica de la DD, sino que también se encuentra presente en TDAH, dependiendo de la superposición de déficits ya que la variabilidad intragrupo DD+TDAH fue muy elevada.…”
Section: Naturaleza De La Comorbilidadunclassified